The Impact of Low Back and Neck Pain on Dentistry Students in Northern Greece. Issue 1 (April 2016) - Stavridis, Stavros I.; Samoladas, Efthimios; Tsitas, Konstantinos; Xanthopoulou, Kassiani; Apostolidou, Kleri; Hatzokos, Ippokratis
Introduction: Dentistry students and dentists comprise a unique group of professionals, whose everyday professional activity requires long hours of standing and working in position considered "unhealthy" for low-bask and neck. The aim of this cross-sectional study was to explore the factors involved in the appearance of low-back and neck pain in dentistry students, as well as the impact of the pain on the students' professional and everyday activities. Materials and Methods: A questionnaire was sent via e-mail to all dentistry students of the 7th, 8th, 9thand 10th semesters (years of clinical practice) of our university. The questionnaire included 43 questions regarding demographical data, history (spinal injury, other comorbidities), daily activities (exercise, smoking, alcohol and caffeine consumption, use of cell phone, etc), professional activities (length and type of dental work), pattern and intensity of pain and personal pain evaluation. A statistical analysis of the gathered data was performed. Results: All students having suffered a spinal trauma or indicating any other comorbidities that could cause severe pain of the spine were excluded from the study. 55 students (21 male, 34 female) were included in the study. Our data showed that increased alcohol consumption and prolonged use of cell phone were connected to increased levels of pain. The students reported that the most frequent onset of pain was one hour after starting to work in standing position, while the majority believed that their working habits were involved in the appearance and the intensity of neck and low-back pain. Conclusions: Our findings indicate that among dentists and dentistry students there appears to be a causative relation between their professional activities and the experienced spinal pain. These findings may be useful in a possible future restructuring of the educational program in dental schools, as well as in improving the ergonomics of dentistry working units.